Use of benzodiazepines in elderly people related fall accidents (Research, Society and Development, 2024)
Objective: This study aims to explore the correlation between the use of benzodiazepines and the incidence of falls in the elderly, with specific focus on the dosage and duration of treatment, as well as the varied pharmacological properties of these medications. Method: An integrative literature review was conducted in various recognized databases, including Google Scholar, LILACS, PUBMED, SciElo, Web Of Science, Scopus, and the CAPES Periodicals Portal. This process resulted in the selection of 10 articles that met the established inclusion criteria for the study. Results: The findings revealed a high prevalence of benzodiazepine use among the elderly population. A significant correlation was identified between the use of these medications and an increase in the incidence of falls in the elderly, with the risk varying between 30% to 60% compared to those who do not use benzodiazepines. Moreover, the analysis pointed to the importance of dosage and treatment duration in the context of geriatric medicine, considering the increased risks for this population. Conclusion: The findings of this study emphasize the need for a careful and individualized approach in prescribing benzodiazepines for the elderly. Health professionals must be aware of the associated risks and exercise strict control in prescribing, evaluating each patient individually and considering therapeutic alternatives. Awareness of the heightened risk of falls associated with the use of benzodiazepines is essential to enhance the safety and well-being of the elderly. This study highlights the importance of evidence-based prescribing practices and a holistic approach in the care of this population.